BAHASA HAMAP DALAM MASYARAKAT MULTILINGUAL DI ALOR DAN UPAYA PELESTARIANNYA - Tondo, Fanny Henry (Jurnal Masyarakat dan Budaya, 2007)
This study talks about multilingual communities in the eastern parts of Indonesia, particularly in Alor Regency, East Nusa Tenggara Province. It focuses on Hamap community and its language in the present actual condition in relation to the language existence in Alor which has multi-ethnic with different languages, specifically in Moru, Alor Barat Daya District. At present, the community is surrounded by some other ethnic groups that have their own languages such as Kui, Abui, and Kelon. In addition, the usage of Hamap language is pressed by Alor Malay as lingua franca in the region. It shows that the language is in a certain degree of extinction process called “potentially endangered language”. These are caused by its minority and the language shift which has occurred in the language community of Hamap, especially in the daily life of its young generation. Nowadays, they would rather speak in Alor Malay than in their own ethnic language. Therefore, all attempts both formal and informal have to be done and supported in order to avoid the language from extinction. Keywords: HAMAP, languages, multilingual community, Alor West Nusa Tenggara